La promoción del cumplimiento normativo: la visión del régimen sancionador administrativo de Ositran y Oefa - Morón Urbina, Juan Carlos; Ortiz Lozada, Carolina Annette (Pontificia Universidad Católica del Perú, 2025)
This article presents a comparative analysis of two models of state regulation: The traditional ‘command and control’ approach, focused on the imposition of sanctions, and the responsive approach, which advocates for a more flexible system based on cooperation, persuasion, and the use of incentives to promote regulatory compliance. Through this comparison, the authors reflect on which model may lead to a more effective and context-appropriate regulatory framework.In this context, the article examines the incentive regimes implemented by the Peruvian regulatory agencies OSITRAN and OEFA, assessing whether they align with the principles of responsive regulation. It analyzes how these mechanisms have been designed, the extent to which they have been implemented in practice, and the key challenges they face in becoming effective tools within the Peru’s regulatory system.

El artículo desarrolla un análisis comparativo entre dos modelos de regulación estatal: el enfoque tradicional de ‘mandato-control’, centrado en la imposición de sanciones, y el enfoque responsivo, que plantea una regulación más flexible, basada en la cooperación, la persuasión y el uso de incentivos para promover el cumplimiento normativo. A partir de esta comparación, se plantea una reflexión sobre cuál de estos modelos permite alcanzar una regulación más eficiente y adaptada a las necesidades del contexto actual. En esa línea, los autores examinan los regímenes de incentivos implementados por los organismos reguladores OSITRAN y OEFA, evaluando si realmente responden a los principios del enfoque responsivo. Se revisa cómo han sido diseñadas estas medidas, su nivel de aplicación práctica en los últimos años y los principales obstáculos que enfrentan para consolidarse como herramientas efectivas dentro del sistema regulatorio peruano.
Enforcing compliance: the vision of the national administrative sanctioning regime of Ositran and Oefa
Keywords: Regulation; Regulatory compliance; Incentives; Sanctions; Responsive approach; Regulación; Cumplimiento normativo; Incentivos; Sanciones; Enfoque responsivo; https://purl.org/pe-repo/ocde/ford#5.05.01